Administration Of Aloe Vera Extract (Aloe Vera L.) Effectively Inhibits The Growth Of The Fungus Malassezia Furfur Causing The Occurrence Of Pythriaasis Versicolor In Vitro - Nasution, Nabila Hani; Lubis, Riri Arisanty Syafrin (Buletin Farmatera, 2026)
Abstract: Pytiriasis versichloror, or better known as panu, is a skin infection caused by a superficial fungus, Malassezia furfur. This disease causes skin discolouration, accompanied by itching in the infected area. Although not contagious, pityriasis versichloror occurs in adolescents or young adults, with risk factors including tropical climate, individual hygiene, environmental factors, age, sex, and genetic factors. Herbal plants, such as aloe vera (Aloe vera L.), have potential as an alternative treatment. Aloe vera has a wide variety of ingredients such as quinones, saponins, aminoglycosides, caffeine, tannins, salicylic acid, flavonoids, synaptic acid, essential oils, and sulfur, some of which have antifungal properties. Previous research has shown that aloe vera extract has an inhibitory effect on the growth of Malassezia furfur fungus. This study aims to determine the effectiveness of giving aloe vera extract (Aloe vera l.) on the growth of the fungus Malassezia furfur, which causes versichloror pityriasis in vitro. This study is an experimental research with a posttest-only control group design. Research shows that the administration of aloe vera extract has a positive impact on inhibiting the growth of Malassezia furfur fungus. Statistical analysis using the Mann-Whitney test confirmed that aloe vera extract effectively inhibited the growth of the fungus. The 90% concentration of aloe vera extract showed the best inhibition effect compared to the concentrations of 80% and 85%. This study shows that aloe vera extract has the potential as an antifungal agent to treat versicolor pityriasis. The 90% concentration of aloe vera extract showed the best inhibition effect, and these findings could be the basis for the development of new therapies in the treatment of versicolor pityriasis using aloe vera extract.